(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Since the Fukushima Daiichi accident, external events analysis has become a priority issue within regulatory bodies, operators, and designers, raising concerns about the capabilities of nuclear power plants to withstand severe conditions. Generally, the methodology applied to the Probabilistic Safety Assessment (PSA) of external events consists of the identification of potential single and combined external hazards, screening of external hazards, analysis of site and plant response, analysis of initiating events and quantification of accident sequences probabilities. Therefore, in this paper, the requirements and other information on new nuclear installations projects necessary to implement a comprehensive PSA of external events throughout plant lifetime are evaluated. In addition, it is necessary to clearly identify all the resources that must be available to continuously expand PSA scope to include all types of initiating events, levels of analysis and plant operation modes.